Transformational and Transactional Leadership on Information Communication Technology (ICT) Implementation in UUM an International UUM Postgraduate Perspectives - Dakhil, Mohamed Hamed (2008)
The topic of this paper is “Transformational and Transactional Leadership on Information Communication Technology (ICT) Implementation in UUM”. Nowadays, there has been an exponential growth in the use of information and communication technology (ICT) which has made pervasive impacts both on society and on our daily lives. The rapid evolution of technology has necessitated a change of approach to corporate technology management especially education institutions. Many education institutions especially in the university implement ICT to improve learning; the emergence of the knowledge economy has also brought about a much greater emphasis on education. ICT means different things to different people. It’s understandable. The ability to develop and articulate a vision of how ICT could produce changes is a critical element in ICT leadership. Successful implementation of change ICT is not about equipment or software but influencing and empowering leaderships; it is not about acquiring computer skills, but supporting leaders in the ongoing engagement with students in their learning. Universiti Utara Malaysia had established the used of ICT system. However, the actual information leadership practice towards the adoption of the ICT implementation in Universiti Utara Malaysia still unclear. It is imperative to evaluate the study and find out the postgraduate perspective on the leadership and ICT implementation in university itself. By investigating the international postgraduate experiences of those implementing ICT, Therefore, the aim of the research is to study and analyzing international postgraduate students’ leadership practice towards the adoption on ICT in Universiti Utara Malaysia. Knowing exactly how international postgraduate students feel about educational technology will permit to manage the psychological aspects of the process and offer motives for the adoption and use of education technology. In our study, we determined the types of application student used in ICT, the adoption levels of ICT among the students, examine international postgraduate leaderships; toward ICT and the relationships between leadership and adoption. 471 population of International postgraduate students were participated in this study. The study was used A research survey was carried out in University Utara Malaysia (UUM) by using questionnaires method to collect data. Our results we described by statistically program, SPSS by using paired t-test. From our study, we found that international postgraduate students at UUM Malaysia have been exposed to some parts of the features offered by UUM Online system.